Co-synthesis of CuO-ZnO nanoflowers by low voltage liquid plasma discharge with brass electrode - Li, Chaojiang (2021)
Transition metal oxides CuO-ZnO nano-flowers have been simultaneously synthesized by the low voltage liquid plasma discharge method using brass cathode. The effects of discharge statue (normal and abnormal glow discharge) on the nanostructures were investigated. It was found that a lower discharge voltage 52 V in the normal glow discharge period is beneficial to produce homogeneous nano-flower structures while a higher voltage tend to result in inhomogeneous products including larger particles. The obtained products were characterized by SEM, XRD, high-resolution TEM, Raman and XPS. Moreover, the nano-flowers exhibit a favorable electrocatalytic activity of glucose oxidation.